Becoming Secondary Survivors: Exploring the Effects of Conflict-Related Sexual Violence on the Health and Well-Being of Families in Northern Uganda - Woldetsadik, Mahlet A. (Journal of interpersonal violence, 2023)
The enduring consequences of conflict-related sexual violence (CRSV) and its catastrophic effects on the health and well-being of survivors has been well documented. However, there is a dearth of evidence on the impact of CRSV on families of survivors who care for them. The aim of this study was to explore the ripple effects of CRSV on families of survivors living in three post-conflict districts in northern Uganda: Gulu, Lira, and Pader. We present emerging themes from qualitative interviews with 22 family members including parents, siblings, and partners. Interviews were recorded, transcribed verbatim, translated to English, and imported into MAXQDA Analytics Pro 12. We used a modified approach to grounded theory to analyze the data. Our findings show that family members faced multiple challenges as a result of their indirect exposure to survivors that were abducted by the Lord’s Resistance Army. These included negative impacts on their relationship with the survivor, secondary traumatic stress, stigma, and challenges with caring for children born in captivity. Participants also shared coping mechanisms they used to mitigate psychological distress, including focusing on their faith, seeking support from social connections, and memory repression. The interviews revealed that most female participants did not seek formal care because they feared stigma and did not think it would be available for individuals not directly affected by sexual violence. Our findings point to the importance of moving beyond a narrow focus on the impact of CRSV on survivors and health care workers to a broader view of understanding the effects on families, and designing interventions that address their needs. Integrating care for families and other informal caregivers might mitigate secondary trauma, and ensure individuals are emotionally protected and equipped to care for survivors.